A Predictive Score for Thrombosis Associated with Breast, Colorectal, Lung, or Ovarian Cancer: The Prospective COMPASS–Cancer‐Associated Thrombosis Study - Gerotziafas, Grigoris T.; Taher, Ali; Abdel‐Razeq, Hikmat; AboElnazar, Essam; Spyropoulos, Alex C.; El Shemmari, Salem; Larsen, Annette K.; Elalamy, Ismail; Gligorov, Joseph; Lotz, Jean Pierre; Mahé, Isabelle; Bachour, Marwan (The oncologist (Dayton, Ohio), 2017)
Background The stratification of outpatients on chemotherapy for breast, colorectal, lung, and ovarian cancers at risk of venous thromboembolism (VTE) remains an unmet clinical need. The derivation of a risk assessment model (RAM) for VTE in these patients was the aim of the study “Prospective Comparison of Methods for thromboembolic risk assessment with clinical Perceptions and AwareneSS in real life patients–Cancer Associated Thrombosis” (COMPASS–CAT). Patients and Methods The derivation cohort consisted of 1,023 outpatients. Patients on low molecular weight heparin (LMWH) thromboprophylaxis were excluded. Documented symptomatic VTE was the endpoint of the study. Results Patients had breast (61%), colorectal (17%), lung (13%), or ovarian cancer (8.6%) at localized (30%) or advanced stage (70%). In 64% of patients, cancer was diagnosed within the last 6 months prior to inclusion. Most of them were on chemotherapy when assessed. Symptomatic VTE occurred in 8.5% of patients. The COMPASS–CAT RAM includes the following variables: (a) anthracycline or anti‐hormonal therapy, (b) time since cancer diagnosis, (c) central venous catheter, (d) stage of cancer, (e) presence of cardiovascular risk factors, (f) recent hospitalization for acute medical illness, (g) personal history of VTE, and (h) platelet count. At 6 months, patients stratified at low/intermediate and high‐risk groups had VTE rates of 1.7% and 13.3%, respectively. The area under the curve of receiver operating characteristics analysis was 0.85. The sensitivity and specificity of the RAM were 88% and 52%, respectively. The negative and positive predictive values of the RAM were 98% and 13%, respectively. Conclusion The COMPASS–CAT RAM includes reliable and easily collected VTE risk predictors and, in contrast to the Khorana score, it is applicable after the initiation of anticancer treatment in patients with common solid tumors. Its robustness for stratification of patients at high and low/intermediate VTE risk needs to be externally validated. Implications for Practice The Prospective Comparison of Methods for thromboembolic risk assessment with clinical Perceptions and AwareneSS in real life patients–Cancer Associated Thrombosis (COMPASS–CAT) study provides a new risk assessment model (RAM) for venous thromboembolism (VTE) applicable in outpatients with breast, colorectal, lung or ovarian cancer. The COMPASS–CAT RAM is robust, applicable during chemotherapy and determines the need for VTE prévention by including reliable and easily collected VTE predictors associated with cancer status, its treatment as well as with patients' characteristics and comorbidities. An independent external validation of the RAM is indicated before its use in clinical practice. The COMPASS‐CAT study was undertaken in outpatients with breast, colon, lung, or ovarian cancer. The aim of the study was to identify the most relevat risk factors for symptomatic thromboembolism and to develop a risk assessment model applicable to patients after the initiation of anticancer treatment.